Overcoming vincristine resistance in cancer: Computational design and discovery of piperine‐inspired P‐glycoprotein inhibitors. (26th July 2020) - Syed, Safiulla Basha; Lin, Shu‐Yu; Arya, Hemant; Fu, I‐Hsuan; Yeh, Teng‐Kuang; Charles, Mariasoosai Ramya Chandar; Periyasamy, Latha; Hsieh, Hsing‐Pang; Coumar, Mohane Selvaraj
Abstract: P‐glycoprotein (P‐gp)/MDR‐1 plays a major role in the development of multidrug resistance (MDR) by pumping the chemotherapeutic drugs out of the cancer cells and reducing their efficacy. A number of P‐gp inhibitors were reported to reverse the MDR when co‐administered with chemotherapeutic drugs. Unfortunately, none has approved for clinical use due to toxicity issues. Some of the P‐gp inhibitors tested in the clinics are reported to have cross‐reactivity with CYP450 drug‐metabolizing enzymes, resulting in unpredictable pharmacokinetics and toxicity of co‐administered chemotherapeutic drugs. In this study, two piperine analogs (3 and 4 ) having lower cross‐reactivity with CYP3A4 drug‐metabolizing enzyme are identified as P‐glycoprotein (P‐gp) inhibitors through computational design, followed by synthesis and testing in MDR cancer cell lines over‐expressing P‐gp (KB Ch R 8–5, SW480‐VCR, and HCT‐15). Both the analogs significantly increased the vincristine efficacy in MDR cancer cell lines at low micromole concentrations. Specifically, 3 caused complete reversal of vincristine resistance in KB Ch R 8–5 cells and found to act as competitive inhibitor of P‐gp as well as potentiated the vincristine‐induced NF‐KB‐mediated apoptosis. Therefore, 3 ((2 E, 4 E )‐1‐(6, 7‐dimethoxy‐3, 4‐dihydroisoquinolin‐2(1 H )‐yl)‐5‐(4‐hydroxy‐3‐methoxyphenyl)penta‐2, 4‐dien‐1‐one) can serve as a potential P‐gp inhibitor for in vivo investigations, to reverse multidrug resistance in cancer. Abstract : Piperine inspired analog 3, reverses vincristine resistance by inhibiting P‐gp efflux and also by potentiating NF‐Kb mediated apoptosis.